Understanding mathematical concepts in students with borderline intellectual functioning: Insights from representational gestures - Elvierayani, Rivatul Ridho; Lusiana, Restu; Suwandayani, Beti Istanti; Silvia, Ifroha Anita (Jurnal Elemen, 2025)
When solving problems, the spontaneous actions of students identified as slow learners (SL) often reflect their cognitive limitations. This study analyzed students' SL understanding of mathematical concepts through representational gestures as a means of communication in constructing concepts. A qualitative case study was conducted in a public junior high school in Lamongan Regency. From eight SL students identified through IQ tests and teacher interviews, only three consistently used representational gestures and were selected as the subjects. Although limited, this sample enabled an in-depth analysis while acknowledging restricted generalization. Data were collected through functional tasks, gesture observations, and interviews and were then analyzed interactively through data reduction, display, and conclusion drawing. The results showed that SL students frequently used hand gestures to represent graph axes or intersection points but misinterpreted variable relationships. They could only classify objects based on conceptual conditions, while other indicators of understanding were not attained. These findings suggest that teachers should consider students’ gestures not only as spontaneous expressions but also as diagnostic cues for misconceptions and as a support for mathematical communication.